Factors Causing The High Number Of Golput In North Jakarta In The 2024 Jakarta Regional Election - Nadia Ayu Lestari; Abdul Ghofur (UNIVERSITAS PAKUAN, 2026)
This study analyzes the factors behind the high abstention (golput) rate in the 2024 Regional Head Election (Pilkada) of DKI Jakarta, focusing on North Jakarta. The abstention rate reached 47,07%, the highest in DKI Jakarta, indicating low political participation and raising concerns about the quality of local democracy. This research uses a qualitative approach with data collected through interviews and literature review. The analysis applies political participation theory. The findings show that abstention is influenced by socio-economic, psychological, rational, and technical factors. Psychological aspects, such as apathy and low trust in candidates, are the most dominant. Technical barriers, including limited access to polling stations, also contribute. Additionally, both active and passive abstention are identified, driven by political fatigue and ineffective electoral outreach. The study concludes that abstention is shaped not only by individual factors but also by structural conditions, highlighting the need for more effective strategies to increase political participation. Keywords: Abstention, Political Participation, 2024 Regional Election.